Thieme Chemistry Journals Awardees – Where Are They Now? Bis(2-pyridyl)amides as Readily Cleavable Amides Under Catalytic, Neutral, and Room-Temperature Conditions - Adachi, Shinya; Kumagai, Naoya; Shibasaki, Masakatsu (Synlett, 2018)
Mild solvolytic cleavage of bis(2-pyridyl)amide under neutral and room-temperature conditions is described. The inherently stable amide was readily activated by catalytic amounts of metal cations to react with alcohols. Based on X-ray crystallographic analysis, the primary driving force was considered to be amide distortion induced by the metal coordination of two pyridyl groups in a bidentate fashion without affecting the amide functionality. The compatibility of the acid/base-sensitive functionalities and the absence of racemization during solvolysis highlight the mildness of the present protocol.
Keywords: amide; deconjugation; amide distortion; amide twisting; solvolysis; metal coordination; mild conditions